Outsourcing in Brazil: Evaluation of legal framework and comments about bill no 4.330/2004 - André Gambier Campos (Institute for Applied Economic Research (ipea), 2016)
Outsourcing may have several impacts in Brazilian labor market, especially for workers. That's why it is relevant to debate new regulations for this phenomenon, mainly legislative ones. The Bill no 4.330/2004 is one of the regulations that have been discussed in the Brazilian parliament. But there are doubts whether this bill is the best option for a legislative regulation of outsourcing. Probably, qualified impact evaluations of this phenomenon should be made, before any parliament's decision about all this.
Keywords: K00; K19; K31; 330; labor market; outsourcing; regulation